2019
DOI: 10.1007/s40145-019-0314-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the sintering technique on the ferroelectric and d33 piezoelectric coefficients of Bi0.5(Na0.84K0.16)0.5TiO3 ceramic

Abstract: In the search of lead-free piezoelectric materials, ceramic processing techniques offer potential tools to increase the piezoelectric and ferroelectric properties in addition to new chemical compositions. Powders of pure BNKT16 (Bi 0.5 (Na 0.84 K 0.16 ) 0.5 TiO 3 ) phase were synthesized by sol-gel method with a low crystallization temperature (750 ℃ ). Ceramic samples were sintered by pressureless sintering (PLS), sinter-forging (SF), and spark plasma sintering (SPS) techniques. Structural, morphological, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Table 3 shows the parameters for Equations (23) and (24). The SOVS model density dependence is fitted to the Scherer model density curve by adjusting the reference viscosity to 𝜂 0 = 3.78 × 10 −13 Pa∕s and the activation energy 𝑄 = 250 kJ∕mol following Equation (18). The difference in the numerical values for the reference viscosity and the activation energy between the "S" and "SOVS" models is a result of the differences in how viscosity has been introduced in the two models.…”
Section: Constitutive Parameters For Viscous Materialsmentioning
confidence: 99%
“…Table 3 shows the parameters for Equations (23) and (24). The SOVS model density dependence is fitted to the Scherer model density curve by adjusting the reference viscosity to 𝜂 0 = 3.78 × 10 −13 Pa∕s and the activation energy 𝑄 = 250 kJ∕mol following Equation (18). The difference in the numerical values for the reference viscosity and the activation energy between the "S" and "SOVS" models is a result of the differences in how viscosity has been introduced in the two models.…”
Section: Constitutive Parameters For Viscous Materialsmentioning
confidence: 99%
“…Among all of the EC materials, a ferroelectric nanocomposite is one of the most promising electrocaloric refrigeration materials, which is an alternative to replace the traditional refrigerator and the air conditioner compressor due to its good adiabatic temperature changes (Δ T ), isothermal entropy (Δ S ), and significantly improved efficiency of thermal cooling . In addition, ferroelectric materials play a vital role in enhancing the performance of composite materials. To complete the design of high-performance electrocaloric devices for advanced flexible cooling systems, it is crucial to comprehensively consider the optimization of composite materials, structural design of the nanocomposite, and device integration. A giant ECE requires a large entropy change correlated with the polarization change.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in the literature on the modifications of the composition of BNT to overcome the drawbacks and to improve its piezoelectric properties 5–10 . Most of these studies are centered on the substitution of Na + by K + in Bi 0.5 (Na 1‐ x K x ) 0.5 TiO 3 , and these compositions are considered as potential candidates for various piezoelectric applications 11–23 . Sasaki et al studied the structural, dielectric, and piezoelectric properties of Bi 0.5 (Na 1‐ x K x ) 0.5 TiO 3 solid solution series and found the morphotropic phase boundary (MPB) region in the range x = 0.16‐0.20 and the piezoelectric properties are maximum in this compositional range 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Most of these studies are centered on the substitution of Na + by K + in Bi 0.5 (Na 1x K x ) 0.5 TiO 3 , and these compositions are considered as potential candidates for various piezoelectric applications. [11][12][13][14][15][16][17][18][19][20][21][22][23] Sasaki et al studied the structural, dielectric, and piezoelectric properties of Bi 0.5 (Na 1-x K x ) 0.5 TiO 3 solid solution series and found the morphotropic phase boundary (MPB) region in the range x = 0.16-0.20 and the piezoelectric properties are maximum in this compositional range. 18 Many other studies have also reported on the enhanced piezoelectric and dielectric performances of Bi 0.5 (Na 1-x K x ) 0.5 TiO 3 in the MPB region.…”
mentioning
confidence: 99%